New airway device as good as tracheal tube insertion for out-of-hospital resuscitation. (13th February 2019) - Cook, Rob; Thomas, Vaughan; Martin, Rosie
The study: Effect of a strategy of a supraglottic airway device versus tracheal intubation during out-of-hospital cardiac arrest on functional outcome: the AIRWAYS-2 randomised clinical trial Benger JR, Kirby K, Black S, Brett SJ, Clout M, Lazaroo MJ, Nolan JP, Reeves BC, Robinson M, Scott LJ, Smartt H, South A, Stokes EA, Taylor J, Thomas M, Voss S, Wordsworth S, Rogers CA Published on 28 August 2018 JAMA 2018;320:779-91 This study was funded by the National Institute for Health Research Health Technology Assessment Programme (project number 12/167/102). To read the full NIHR Signal, go to: https://discover.dc.nihr.ac.uk/content/signal-000686/new-airway-device-as-good-as-tracheal-tube-for-resuscitation-out-of-hospita